Independent high voltage DC source development for renewable-grid integration interface - Omar Abu Hassan; Shamsul Aizam Zulkifli; Mohd Shamian Zainal; Ahmad Alabqari Ma' Radzi; Muhammad Shukri Ahmad; Tengku Nadzlin Tengku Ibrahim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Recent advancement in renewable-grid integration research, due to the concern on the environmental impact, leads to extensive study in isolated power converter as their interface. As part of isolation capability in power converter interface, extensive study of magnetic component has been carried out, especially on the design, construction and optimisation to achieve optimal operation. One of the main issue in verifying the analytical power loss model is to have independent HVDC link power source for an experimental validation work. This paper focus on the design and construction of DC link source, to be use in the experimental rig setup. Several DC link source option has been evaluated, and TDK-lambda PF500-360A power supply was selected due to the availability and excellent energy efficiency offered, at better price. External circuit is designed and implemented to achieve desired voltage and current supply characteristic. At the end, the voltage and current of the DC link supply for Dual H-bridges is obtained and shown promising result for experimental rig measurement and data collection work.